MOTIF DAN MAKNA PROFESI BIKE MESSENGER BAGI ANGGOTA WESTBIKE MESSENGER SERVICE JAKARTA - Maulana Naseem Alwi; Siti Nursanti; Wahyu Utamidewi (Metacommunication: Journal of Communication Studies, 2021)
The increasing congestion in the capital city of Jakarta demands new solutions and innovations in the delivery of goods or documents. From this problem, the company Westbike Messenger Service emerged as a service provider for goods delivery using bicycles. Making the birth of a new profession, namely bike messenger, is a unique profession because usually courier services for delivery of goods use motorized vehicles. The researcher aims to determine the motives and meaning of the bicycle courier profession for members of the Westbike Messenger Service in Jakarta. This research method uses a qualitative method with a phenomenological approach, because the researcher tries to find out the phenomena from the direct experience of the informants, as well as the motives and meanings of the informants living their profession. The data obtained by the researcher were obtained through in-depth interviews, observation, and document study. The results of the study show first, the motive for choosing the bike messenger profession due to economic factors, the hobby of cycling, just experimenting, and suggested by friends. Second, the motive for (in-order-to motive), namely for career advancement, own income, producing hobbies, and wanting to be like a foreign courier. Third, the meaning of the bike messenger profession as his love for bicycles and a productive hobby.